Pengaruh Kompetensi Aparatur Pemerintah Desa, Partisipasi Pengguna, dan Usability System Terhadap Efektivitas Penerapan Sistem Keuangan Desa (Siskeudes) - Suryaningsih, Ni Komang; Adiputra, Made Pradana (Universitas Pendidikan Ganesha, 2020)
The aim of this study was to prove empirically the effect of the competence of village government apparatus, user participation, and usability system toward the effectiveness of the implementation of Siskeudes in Buleleng Regency. This research was a quantitave research with a primary data acquired from questionnaire and measured use Likert scale and secondary data in the form of recipient villages in the village budget allocation for fiscal year 2019. The population were all village secretaries, financial staff and village operator staff in Buleleng Regency. Samples in this study were 168 people and selected using proportional random sampling technique. The data analysis technique used multiple linear regression analysis with the help of SPSS version 24. The results showed that the competency variable of the village government apparatus (X1) had a positive and significant effect toward the effectiveness of the implementation of Siskeudes, the variable of user participation (X2) had a positive and significant effect toward the effectiveness of the implementation of Siskeudes, the usability system variable (X3) has a positive and significant effect toward the effectiveness of the implementation of Siskeudes.